OPTIMALISASI MEDIA PEMBELAJARAN INTERAKTIF DALAM MATA PELAJARAN TARIKH DI SMA MUHAMMADIYAH 1 SIMO BOYOLALI TAHUN PELAJARAN 2024/2025 - Kultsum, Ummi; Muslimin, Edy (STKIP Pesisir Selatan, 2025)
The advancement of information technology has significantly influenced educational practices, including Islamic history (Tarikh) learning. Interactive learning media has emerged as a strategic alternative to enhance the quality and effectiveness of instruction, especially in simplifying complex historical content. This study aims to describe the implementation of interactive learning media in Tarikh subjects among 11th-grade students at SMA Muhammadiyah 1 Simo Boyolali and to analyze its effectiveness in improving student comprehension and learning motivation. This research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation, then analyzed thematically. The findings reveal that teachers utilize various interactive media such as dynamic PowerPoint presentations, historical videos, digital quizzes, and Google Classroom. These media have been effective in increasing student participation, enhancing understanding of historical concepts, and creating an engaging and meaningful learning environment. Despite technical challenges, solutions were made possible through teacher initiatives and school infrastructure support. The results indicate that interactive learning media serves as an effective strategy to improve Tarikh learning outcomes.